Albania : Fifth and Sixth Review under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Albania. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
Background: In February 2014, the Executive Board approved a three-year Extended Arrangement with access equivalent to SDR 295.42 million (492.4 percent of quota). So far, four purchases totaling the equivalent of SDR 123.1 million have been made, and another one equivalent to SDR 57.76 million will be made available upon completion of the fifth and sixth reviews. Recent Economic Developments: Economic recovery is underway, but growth remains below potential and inflationary pressures are limited. Nonperforming loans (NPLs) have started declining but are still high, and credit growth remains sluggish despite substantial monetary easing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet